Effect of Cerium on the Electrical Properties of a Cobalt Conversion Coating for Solid Oxide Fuel Cell Interconnects – A Study Using Impedance Spectroscopy. (1st December 2015) - Grolig, Jan Gustav; Froitzheim, Jan; Svensson, Jan-Erik
Abstract: Coatings of metallic cobalt, which convert into a cobalt manganese spinel oxide are known to improve the properties of interconnects for solid oxide fuel cells (SOFCs). The addition of cerium to the cobalt coating further improves the corrosion properties of the material. For this study traditional four-point DC measurements at high temperatures were combined with impedance spectroscopy at low temperatures in order to investigate the effect of cerium on the electrical properties of a cobalt conversion coating. It was found that combination-coatings of cerium and cobalt exhibit superior electrical properties compared to pure cobalt coatings. Cerium slows down the growth of chromia and prevents the outward diffusion of iron into the cobalt spinel layer. Both effects are beneficial for the electrical properties of the interconnect. Impedance spectroscopy measurements revealed that even after more than 3000 h of exposure the outer cobalt manganese spinel layer still has a higher electrical conductivity when cerium was present.